Prevalence of caesarian section among primigravida women in Shahr-Ara teaching hospital Kabul, Afghanistan - Aram, Fahima; Saiqal, Oniba (Technium BioChemMed, 2022)
Caesarian section is defined as a surgical procedure carried out on the abdomen and uterus of the mother to deliver one or more than one fetus and most of the time it is carried out when the survival of mother or fetus is in danger and sometime it is carried on mothers own choice. Aim: The aim of this study is to know the prevalence of caesarian section among the primigravida women visiting shahrara teaching hospital. Method. This research was done as descriptive cross sectional study such that the prevalence of caesarian section among primigravid women who visited shahrara teaching hospital at the first six months of the year 1396. Result: In this research caesarian section was done on 29 women making 38.15 % with gestational age of 28 weeks out of total 76 primigravid women. Median age was 23.34±4 (±SD), age range was 17-35 years, and majority of the case was at ages 21-25 years. Average age of the newborn was 3.88±0.436(0.436(±SD) kilogram, and weight range was 2-4.5 kilgram. Among 75.86% of primigravid women caesarian section was done on emergency bases and about 3.44 percent of women experienced hemorrhage during surgery. The percentage of babies with low APGAR score 13.79 percent. 27.58 percent of women had oligohdromnios and 17.24 percent had premature rupture of amniotic membrane (PROM). Incidence of breech presentation was about 6.89% and 24.13 percent had cranio pelvic disproportion (CPD). 3.44percent had twin pregnancy. Conclusion: It was concluded in this research that the prevalence of caesarian section among primigravid women was 38.15 percent and the incidence increases at age range of 21-25 years. Although caesarian section is considered a lifesaving procedure for mother and newborn it must be carried out on logical and appropriate bases among the primigravid women.